2014
DOI: 10.4236/ojas.2014.43016
|View full text |Cite
|
Sign up to set email alerts
|

Tree-Fall Gaps Effects on Spider (Araneae) Assemblages in an Atlantic Forest Landscape in Northeastern Brazil

Abstract: The study investigates the effect of spatial and temporal tree-fall gaps structure on spiders' assemblage in an Atlantic forest fragmented area in Brazil. It was conducted in the Michelin Ecological Preserve-REM (Bahia), 190 ha forest remnant. Samples were collected on leaf-litter (50 × 50 cm) at five tree-fall gaps formations (<150 m 2), within five adjacent primary forest and five inner edge parcels. During 16 months (between May 2009 and October 2012), 480 m 2 leaf-litter samples were collected, from which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These studies revealed significant differences in the structure and composition of the birds and weaver's spider's assemblages between these two environments [7,22]. Studies also revealed spatio-temporal influence of Treefall Gaps on spider's assemblage [23]. For ants, the results were conflicting.…”
mentioning
confidence: 55%
“…These studies revealed significant differences in the structure and composition of the birds and weaver's spider's assemblages between these two environments [7,22]. Studies also revealed spatio-temporal influence of Treefall Gaps on spider's assemblage [23]. For ants, the results were conflicting.…”
mentioning
confidence: 55%
“…Meanwhile, the majority of orb-weaver spiders are associated with more stable microclimatic conditions under more closed canopies. Araneidae and Tetragnathidae are major orb weavers with a strong dependence on relative humidity (Peres et al 2014). The prey-capture threads in most spider orb webs greatly depend on viscous droplets for their stickiness, and therefore, the droplet extensibility becomes more intense with increasing humidity (Opell et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high herbaceous vegetation coverage together with fallen trunks constitute a suitable booster and support for fixing the spiders' webs. Consequently, based on the distinctiveness of microhabitats and microclimate created by the amount of light perceived, forests and non-forests systems are differently constituted in terms of Araneae abundance (Peres et al, 2014).…”
Section: Soil Macrofauna Abundance and Diversity In Different Tree Sp...mentioning
confidence: 99%